Adaptations of Scrum Roles in Software Projects: Survey and Representation Tentative with Feature Models - Garcia, Luciano A.; OliveiraJr, Edson; Leal, Gislaine Camila L.; Morandini, Marcelo; Urbanowski, Shayne (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Scrum is one of the most popular agile methods due to its framework structure. This structure allows flexibility to adapt to project characteristics. Given this, expected adaptations in the Scrum elements is something natural. Roles are one of these elements. They are of great importance in the successful deployment of Scrum. Therefore, we expect to understand the extent of the adaptations practiced in the Scrum roles Scrum Master, Product Owner, and Development Team by conducting a survey with practitioners. To better comprehend such adaptations and their relationships, we decided to systematize, group, and represent them using a feature model. We, then, evaluated the created feature model inviting Scrum deployment experts. Results point out the feasibility of our feature model based on the perceived usefulness and ease of use. Such model makes it possible for practitioners to have a set of features they can instantiate and customize according to their needs and recommendations from the Scrum guide. Another benefit of such feature model is that it records Scrum users' background and compares similar situations where certain features have been adopted.